2022
DOI: 10.1007/s12144-022-03876-4
|View full text |Cite
|
Sign up to set email alerts
|

The positive energy of netizens: development and application of fine-grained sentiment lexicon and emotional intensity model

Abstract: The outbreak of COVID-19 has led to a global health crisis and caused huge emotional swings. However, the positive emotional expressions, like self-confidence, optimism, and praise, that appear in Chinese social networks are rarely explored by researchers. This study aims to analyze the characteristics of netizens' positive energy expressions and the impact of node events on public emotional expression during the COVID-19 pandemic. First, a total of 6,525,249 Chinese texts posted by Sina Weibo users were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…We randomly selected the annotation results of 327/4079 (8%) words from the corpora of patients with BC for the annotator consistency test [ 80 ], and the Fleiss κ value was 0.491 (95% CI 0.482-0.501), with moderate strength of agreement, which showed that the annotation results were consistent and the consistency was acceptable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We randomly selected the annotation results of 327/4079 (8%) words from the corpora of patients with BC for the annotator consistency test [ 80 ], and the Fleiss κ value was 0.491 (95% CI 0.482-0.501), with moderate strength of agreement, which showed that the annotation results were consistent and the consistency was acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…See Multimedia Appendix 3 for the number and examples of emotional words based on 8 emotional categories in the emotional lexicon of patients with BC. We randomly selected the annotation results of 1471 of 14,709 sentiment words at a rate of 8% for the annotator consistency test [ 80 ], and the Fleiss κ value was 0.439 (95% CI 0.437-0.441), with moderate strength of agreement, which showed that the annotators’ annotation results were consistent and the consistency was acceptable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By collecting the basic public opinion discussion data of the 'Taocheng Hengshui Middle School Incident' for 15 consecutive days, taking the Weibo Topic readership number, the number of discussions and the number of original people as the life cycle division which is shown in Figure 2, the emotional words were extracted through the emotion dictionary [46], and some of the emotion words, under the artificial annotation of specific comments, were taken as the emotion base words [47]. Then, calculate the semantic similarity [48].…”
Section: The Division Of Rumor Life Cyclementioning
confidence: 99%